Konsep Islamic Wordview Syed Muhammad Naquib Al-Attas dalam Membangun Kultur Keberagamaan Masyarakat Madura - Hamdani, Hamdani; Maimun, Maimun (Nuris Journal of Education and Islamic Studies, 2025)
The Islamic view is the most important thing in all aspects of Madurese society's life, the Islamic conception of aspects of Madurese society's life will give birth to many positive values, especially in building a culture of religion. This study aims to determine the views of Syed Naquib Al-Attas in viewing life or reality, which will later be associated with religious patterns in Madura. This research uses a library research method with primary data sources that focus on Islamic concepts in social life. Primary data sources were obtained from literature, including books, journals, websites that were relevant and in accordance with the study in this research. The results of this study indicate that the concept of Islamic world view of Syed Muhammad Naquib Al-Attas leads to two aspects of religious tradition patterns in Madura: 1) can improve ukhwah: a) Ukhwah islamiyah which consists of religious patterns of moloden, tahlilan, molodhen. b) Ukhwah basyariah which is formed in the tradition pattern of theater with neighbors. c) Ukhwah Wathaniyah which is formed in the culture pattern of nyapot, alabet and urunan. 2) Sharia, which is formed in the tradition of requiring a child to study the Koran at the langghar.